2021
DOI: 10.1021/acsanm.1c01398
|View full text |Cite
|
Sign up to set email alerts
|

Amine-Functionalized Graphene Quantum Dots for Fluorescence-Based Immunosensing of Ferritin

Abstract: The current work demonstrates the fabrication and optimization of a fluorescence-based immunosensor for ferritin estimation wherein amine-functionalized graphene quantum dots (afGQDs) and methyl orange are used as a fluorophore–quencher couple. The synthesis of afGQDs is achieved by the hydrothermal method. The synthesized QDs were characterized using analytical techniques such as UV–vis, fluorescence, FTIR, and Raman spectroscopies, XRD diffraction studies, elemental analysis, and morphological studies throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Graphene is widely used in many applications, such as electronics, solar cells and Li-ion batteries [54], whereas GQDs have attracted tremendous interest in photoluminescence [55], cell-imaging [56] and drug delivery [57,58], among many things. GQDs have a great advantage, as their properties can be adjusted by changing their band via doping to produce amine-functionalised GQDs [59], nitrogen-doped GQDs (N-GQDs) [60] and sulphur-nitrogen co-doped GQDs (S, N-GQDs) [61]. Furthermore, the photoluminescence colour of GQDs can also be changed from violet to yellow by setting the reactant concentration and temperature during the hydrothermal method [54].…”
Section: Graphene Quantum Dots (Gqds)mentioning
confidence: 99%
“…Graphene is widely used in many applications, such as electronics, solar cells and Li-ion batteries [54], whereas GQDs have attracted tremendous interest in photoluminescence [55], cell-imaging [56] and drug delivery [57,58], among many things. GQDs have a great advantage, as their properties can be adjusted by changing their band via doping to produce amine-functionalised GQDs [59], nitrogen-doped GQDs (N-GQDs) [60] and sulphur-nitrogen co-doped GQDs (S, N-GQDs) [61]. Furthermore, the photoluminescence colour of GQDs can also be changed from violet to yellow by setting the reactant concentration and temperature during the hydrothermal method [54].…”
Section: Graphene Quantum Dots (Gqds)mentioning
confidence: 99%
“…The sensors robustness was evaluated with human serum samples and the method displayed a wide linear range. 206 The following points can be concluded from optical based detection:…”
Section: D Layered Materials Based (Bio)sensors For Oxidative Stress ...mentioning
confidence: 99%
“…The fluorescence quenching was observed with methyl orange, which was restored with the interactions of the antigen–antibody@amine functionalized graphene quantum dot probe. The sensors robustness was evaluated with human serum samples and the method displayed a wide linear range …”
Section: D Layered Materials Based (Bio)sensors For Oxidative Stress ...mentioning
confidence: 99%
“…[22][23][24][25] However, versus other conventional macrocyclic hosts, pillar [n] arenes have important properties such as strong bonding guest and high selectivity in host-guest recognition, which have special recognition capabilities in the sensing area. [26][27][28][29] In recent years, some studies have reported fluorescent sensors by combining the outstanding fluorescence quenching ability of graphene [30][31][32][33] and excellent supramolecular recognition efficiency of pillar[n]arenes. [34][35][36][37] Therefore, in light of these significant findings, we develop a highly selective and sensitive fluorescent sensing platform for SC detection based on a cationic pillar [6]arene (CP6)-functionalized reduced graphene (RGO) nano-composite (CP6-RGO) as a receptor and probe rhodamine B (RB) and the sensing system is shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies have reported fluorescent sensors by combining the outstanding fluorescence quenching ability of graphene 30–33 and excellent supramolecular recognition efficiency of pillar[ n ]arenes. 34–37 Therefore, in light of these significant findings, we develop a highly selective and sensitive fluorescent sensing platform for SC detection based on a cationic pillar[6]arene (CP6)-functionalized reduced graphene (RGO) nano-composite (CP6-RGO) as a receptor and probe rhodamine B (RB) and the sensing system is shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%